2017
DOI: 10.1002/ana.25106
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic findings in children with central nervous system arteriovenous fistulas

Abstract: These results highlight the importance of genetic testing in this setting in view of the high frequency of gene mutations in pediatric cerebrospinal AVFs, and show the predominance of RASA1 over HHT mutations. Ann Neurol 2017;82:972-980.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…In patients with documented AVFs, recent data suggest that ≈9% will harbor known mutations. [455][456][457] RASA-1-and HHT-related mutations (ENG and ACVRL1) were most common, with clinical findings including multiple cranial lesions, spinal AVF/AVM, hypercoagulable states, and capillary hemangioma (in RASA-1). 430,455,456,457 Treatment.…”
Section: Genetic Screeningmentioning
confidence: 99%
“…In patients with documented AVFs, recent data suggest that ≈9% will harbor known mutations. [455][456][457] RASA-1-and HHT-related mutations (ENG and ACVRL1) were most common, with clinical findings including multiple cranial lesions, spinal AVF/AVM, hypercoagulable states, and capillary hemangioma (in RASA-1). 430,455,456,457 Treatment.…”
Section: Genetic Screeningmentioning
confidence: 99%
“…88 Additional recent studies demonstrated autosomal dominant EPHB4 mutations, named CM-AVM2. 89 This gene encodes a trans-membrane receptor expressed primarily in venous ECs during vascular development interacting with its ligand, EphrinB2, on arterial ECs. EPHB4 also activates p120-RasGAP, and therefore exerts similar downstream effects on the MEK/ERK pathway as RASA1.…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…Congenital pial AVFs have been linked to various congenital diseases, the commonest of which is hemorrhagic hereditary telangiectasia which co-presents with AVFs in one-quarter of patients ( 41 ). Recent data suggest that ≈9% of patients with AVFs will harbor known mutations ( 41 43 ). RASA-1– and HHT-related mutations (ENG and ACVRL1) were most commonly associated with clinical phenotypes including cranial lesions, hypercoagulable state, spinal AVF/AVM, capillary hemangioma (in RASA-1) ( 15 , 41 43 ).…”
Section: Section 2: Arteriovenous Fistulas (Avfs)mentioning
confidence: 99%